2015
DOI: 10.1016/j.jmii.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus and thyroid disease: A 10-year study

Abstract: SLE patients had a significantly lower rate of thyroid diseases and hyperthyroidism than matched controls. Among SLE patients, risks of hypothyroidism and autoimmune thyroiditis were different in the presence of overlap syndrome. This finding is novel and important for clinical practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 22 publications
5
38
0
1
Order By: Relevance
“…However, discordant results have been recently reported (33). In 1,633 SLE patients of new diagnosis, the prevalence of hyperthyroidism, hypothyroidism, and autoimmune thyroiditis (AT) was compared with 6,532 controls (matched by sex and age).…”
Section: The Association Of Sle and Aitdmentioning
confidence: 64%
See 1 more Smart Citation
“…However, discordant results have been recently reported (33). In 1,633 SLE patients of new diagnosis, the prevalence of hyperthyroidism, hypothyroidism, and autoimmune thyroiditis (AT) was compared with 6,532 controls (matched by sex and age).…”
Section: The Association Of Sle and Aitdmentioning
confidence: 64%
“…The authors suggested that SLE patients had a significantly lower rate of thyroid diseases and hyperthyroidism than matched controls (33). The reported study could have some limitations, able to affect the results, to be considered: (1) it was based on diagnostic codes released from The National Health Insurance Research Database, and for this reason details on thyroid serological assessments, presence of ThyAb, or SLE autoantibodies were not available; (2) data obtained in a retrospective cohort study are usually inferior in statistical quality to those derived from randomized trials because of the potential biases related to adjustments for confounding variables (33). A total of 376 Colombian SLE patients were evaluated for the presence of (1) confirmed autoimmune hypothyroidism (AH), (2) positive AbTPO/AbTg without hypothyroidism, (3) non-AH, and (4) SLE patients with neither.…”
Section: The Association Of Sle and Aitdmentioning
confidence: 99%
“…Even though more recent studies have investigated the relationship between thyroid disease and SLE using data from large populations, they also provide inconsistent and conflicting results. A Taiwanese retrospective nationwide cohort study showed that SLE patients had a significantly lower rate of thyroid disease [15], whereas another recent study in Israel reported that both hyper- and hypothyroidism were associated with SLE [13, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Clustering of multiple autoimmune disorders has been described as a spectrum ranging from involving one organ (such as autoimmune thyroiditis and CLE) to involving multiple organs 15. However, an extensive PubMed search revealed no association between DSH and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%